Alcohol use disorder epidemiology and interventions to support behaviour change - Subhani, Mohsan (2023)
Alcohol is a preventable leading cause of liver disease. In the United Kingdom (UK) 25% of the population drinks above the recommended level and 10% are harmful drinkers. Alcohol-related liver disease (ARLD) progresses silently, over 50% of patients are first diagnosed with liver disease after an emergency hospital admission at a stage when the scope of any medical and behavioural intervention is limited. Though the prevalence of alcohol use disorder is disproportionately higher among hospitalised patients as compared to the community, it is persistently underdiagnosed and undertreated in hospital settings.